Study of Hyperbranched Poly(ethyleneimine) Polymers of Different Molecular Weight and Their Interaction with Epoxy Resin - Román, Frida (Materials (Basel), 2018)
Two different commercial hyperbranched poly(ethyleneimine)s (HBPEI), with molecular weights (MW) of 800 and 25,000 g/mol, and denoted as PEI800 and PEI25000, respectively, as well as the mixtures with a Diglycidyl Ether of Bisphenol-A (DGEBA) epoxy resin, have been studied using thermal analysis techniques (DSC, TGA), dielectric relaxation spectroscopy (DRS), and dynamic mechanical analysis (DMA). Only a single glass transition is observed in these mixtures by DSC. DRS of the HBPEIs shows three dipolar relaxations: γ, β, and α. The average activation energy for the γ-relaxation is similar for all HBPEIs and is associated with the motion of the terminal groups. The β-relaxation has the same average activation energy for both PEI800 and PEI25000; this relaxation is attributed to the mobility of the branches. The α-relaxation peak for all the HBPEIs is an asymmetric peak with a shoulder on the high temperature side. This shoulder suggests the existence of ionic charge trapped in the PEI. For the mixtures, the γ- and β-relaxations follow the behaviour of the epoxy resin alone, indicating that the epoxy resin dominates the molecular mobility. The α-relaxation by DRS is observed only as a shoulder, as a consequence of an overlap with conductivity effects, whereas by DMA, it is a clear peak.